Common fixed points versus best approximations - Latif, Abdul (Tamkang Journal of Mathematics, 2001)
We obtain a common fixed point theorem for (f,g) -nonexpansive maps in p -normed spaces. Some results on best approximation are also derived via common fixed points. Our results generalize and extend the work of Al-Thaghafi [J. Approx. Theory 85 (1996), 318-323], Khan and Khan [Approx. Theory & its Appl., 11 (1995), 1-5], Habiniak [J. Approx. Theory, 56 (1989), 241-244], Sahab, Khan and Sessa [J. Approx. Theory, 55 (1988), 349-351], and many of the others.